Assessment of the quality of life of patients with type 2 diabetes mellitus with diabetic foot syndrome after reconstructive surgery - Shagazatova B.Kh; Artikova D.M; Ishonkulova N.F; Avezova G.S; Artikov A.F; Urunbaeva D.A (Zien Journals, 2022)
Diabetes mellitus (DM) is a paramount and rising medical challenge in both industrial and emerging nations. It represents a serious medical and social problem, which is due not only to its high prevalence, chronic course, which determines the accumulation of a contingent of patients with diabetes, but also to a large number of complications and a high degree of disability.
Keywords: diabetes mellitus; diabetic foot; hyperglycemia; quality of life